Planting Design Expression on Students Perceiving Campus Landscape Quality - Mt Akhir, Norizan; Amir, Atikah Fukaihah; Abdullah, Lizawati; Halim, Deddy Kurniawan (International Journal of Sustainable Construction Engineering and Technology, 2023)
Planting design plays a vital role in evaluating and enhancing landscapes by deliberately arranging and selecting plants within a given area. It encompasses various elements, including plant types, arrangement, density, colour, texture, and composition, all contributing to the visual appeal and aesthetics of green spaces, creating harmonious and visually pleasing environments. Beyond environmental sustainability, planting design also holds significance in promoting aesthetical value for certain spaces. This study focuses on exploring how different planting design approaches impact the students’ expression when perceiving quality of campus green spaces. The objectives are to identify preferences for planting design scenes and investigate the influencing criteria. A Likert-scale questionnaire utilizing 51 planting images from Universiti Putra Malaysia is employed to collect data. The gathered preferences are analysed using IBM SPSS Statistics 23 to determine significant criteria and expression on preferences. The findings emphasize students’ preferences for coherent and balance plant arrangements, naturalness with moderate density and maintenance. The implications of this study will aid campus designers in developing future landscape designs that incorporate preferred planting design characteristics.